Combined exome and whole-genome sequencing identifies mutations in ARMC4 as a cause of primary ciliary dyskinesia with defects in the outer dynein arm. Issue 1 (7th November 2013) - Onoufriadis, Alexandros; Shoemark, Amelia; Munye, Mustafa M; James, Chela T; Schmidts, Miriam; Patel, Mitali; Rosser, Elisabeth M; Bacchelli, Chiara; Beales, Philip L; Scambler, Peter J; Hart, Stephen L; Danke-Roelse, Jeannette E; et al.
Abstract : Background: Primary ciliary dyskinesia (PCD) is a rare, genetically heterogeneous ciliopathy disorder affecting cilia and sperm motility. A range of ultrastructural defects of the axoneme underlie the disease, which is characterised by chronic respiratory symptoms and obstructive lung disease, infertility and body axis laterality defects. We applied a next-generation sequencing approach to identify the gene responsible for this phenotype in two consanguineous families. Methods and results: Data from whole-exome sequencing in a consanguineous Turkish family, and whole-genome sequencing in the obligate carrier parents of a consanguineous Pakistani family was combined to identify homozygous loss-of-function mutations in ARMC4, segregating in all five affected individuals from both families. Both families carried nonsense mutations within the highly conserved armadillo repeat region of ARMC4: c.2675C>A; pSer892* and c.1972G>T; p.Glu658*. A deficiency of ARMC4 protein was seen in patient's respiratory cilia accompanied by loss of the distal outer dynein arm motors responsible for generating ciliary beating, giving rise to cilia immotility. ARMC4 gene expression is upregulated during ciliogenesis, and we found a predicted interaction with the outer dynein arm protein DNAI2, mutations in which also cause PCD. Conclusions: We report the first use of whole-genome sequencing to identify gene mutations causing PCD. Loss-of-function mutations in ARMC4 cause PCD with situs inversus and cilia immotility, associated with a loss of the distal outer (but not inner) dynein arms. This addition of ARMC4 to the list of genes associated with ciliary outer dynein arm defects expands our understanding of the complexities of PCD genetics.